Latin American protected areas: Protected from chemical pollution?. (7th October 2016) - Rodríguez‐Jorquera, Ignacio A; Siroski, Pablo; Espejo, Winfred; Nimptsch, Jorge; Choueri, Paloma Gusso; Choueri, Rodrigo Brasil; Moraga, Claudio A; Mora, Miguel; Toor, Gurpal S
ABSTRACT: Protected areas (PAs) are critically important means to preserve species and maintain natural ecosystems. However, the potential impacts of chemical pollution on PAs are seldom mentioned in the scientific literature. Research on the extent of the occurrence of chemical pollution inside PAs and in‐depth assessments of how chemical contaminants may adversely affect the maintenance of species abundance, species survival, and ecosystem functions are scarce to nonexistent. We investigated 1) the occurrence of chemical contaminants inside 119 PAs in Latin America from publically available databases, and 2) reviewed case studies of chemical contaminants and pollution in 4 Latin American PAs. Cases of chemical pollution and contamination inside Latin American PAs mostly originated from sources such as mining, oil, and gas extraction. To date, the focus of the research on chemical pollution research inside Latin American PAs has been primarily on the detection of contamination, typically limited to trace metals. Where management actions have occurred, they have been reactive rather than proactive. Protected areas established in wetlands are the most affected by chemical pollution. Based on the information from the pollution and/or contamination occurrence and the case studies analyzed, Latin American PAs are not well safeguarded from chemical pollution, resulting in both challenges and opportunities to conserve biodiversity and ecosystems. Integr Environ Assess Manag 2017;13:360–370. © 2016 SETAC Key Points: Despite the fact that chemical pollution can harm free‐range organism populations, research on the impact of chemical pollution inside protected areas (PAs) is rarely considered. Our database review and case studies showed that Latin American PAs are not necessarily safeguarded from chemical pollution. Chemical pollution had affected biodiversity inside Latin American PAs, but management actions to avoid the damage have rarely occurred, and when present, they have been reactive rather than proactive, which is inadequate and inefficient. Aquatic environments might be the most threatened habitats within PAs in Latin America as shown in these database analyses and case studies, thus, PAs established in wetlands are the most vulnerable to chemical pollution.